Analisis Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan Sektor Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016 - Christopher Christopher (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The relationship between capital structure and profitability cannot be ignored because the improvement in the profitability is necessary for the long-term survivability of the firm. This paper seeks to investigate the relationship between capital structure and proﬁtability of listed ﬁrms on the Indonesia Stock Exchange during a three-year period. A sample of 35 Indonesia firms listed on Indonesia Stock Exchange for a period of 3 years from 2014-2016 was selected. The correlations and regression analysis were used to estimate the functions relating to profitability (measured by return on equity) with measures of capital structure. Empirical results show a positive relationship between i) short-term debt to total assets and profitability and ii) total debt to total assets and profitability in the service industry, and negative relationship between long-term debt to total assets and profitability. This paper offers useful insights for the owners/operators, managers, and lending institutions based on empirical evidence, and suggests that proﬁtable ﬁrms depend more on debt as their main ﬁnancing option.